2019
DOI: 10.1002/jssc.201801165
|View full text |Cite
|
Sign up to set email alerts
|

Preparative isolation and purification of steroidal glycoalkaloid from the ripe berries of Solanum nigrum L. by preparative HPLC–MS and UHPLC–TOF‐MS/MS and its anti‐non‐small cell lung tumors effects in vitro and in vivo

Abstract: Overcoming epidermal growth factor receptor resistance is a critical problem that needs to be solved in clinical practice. Drugs that downregulate the fatty acid synthaseepidermal growth factor receptor will become novel treatments for non-small cell lung cancer. Solanum nigrum, extracted with water at 4 • C, shows strong cytotoxic activity and inhibits tumor growth in Lewis tumor bearing-mice in a dose-dependent manner. A novel active compound in S. nigrum, solaoiacid, was successfully separated and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that about 50 homoisoflavoniods were purified and identified by repeated column fractionations [1]. HPLC with diode array detector (DAD) and MS/MS has been developed for rapid isolation and characterization of bioactive components from complex natural products [8–11]. However, information about comprehensive analysis of homoisoflavonoids, especially for minors, in O. japonicus by HPLC–DAD–MS/MS is restricted because of the existence of multicomponents, restriction of detection sensitivity, and coelution of minor and abundant compounds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Both S. nigrum L. extract and the newly identified GA of this plant, solaoiacid, inhibit the FASN-EGFR signaling pathway and affect the migration, autophagy, apoptosis, and immune response of non-small cell lung cancer (NSCLC) cells. Furthermore, solaoiacid acts with an IC 50 = 2.3 μmol/L, which is significantly lower than that of SM (Shi et al, 2019). The extract of S. nigrum L. had antitumor effects on rat C6 MG in vitro and in vivo.…”
Section: Crude Extracts Of Solanaceae Plantsmentioning
confidence: 87%
“…According to the literature [15][16][17], the steroidal glycoalkaloids from S. nigrum are composed of seven basic types of aglycones (including isomers), namely, solasodine (S), hydroxysolasodine (HS), hydroxymethylsolasodine (HMS), dihydroxymethylsolasodine (DHMS), carboxylsolasodine (CS), and hydroxycarboxylsolasodine (HCS) linked with glycosyl groups, which are made up of hexoses, such as glucose (Glc) and galactose (Gal), 6-deoxyhexoses, such as rhamnose (Rha), pentoses, such as xylose, and uronic acids, such as glucuronic acid (GlcA) and galacturonic acid (GalA), through ether glycosidic bonds at carbon-3 of the aglycones. Substitution of groups on the steroid skeleton often occurs at carbon-7α (B-ring), carbon-12β (C-ring), and carbon-27 (F-ring) sites.…”
Section: Rationale For Structural Characterizationmentioning
confidence: 99%
“…At present, most of the steroidal glycoalkaloids identified in Solanum nigrum fruit are monoglycosides, diglycosides, and triglycosides with molecular weights less than 1000 Da with solasodine or its substitute as the aglycone [7 -10]. The alkaloids found include solasodine, khasianine, solasonine, solamargine, solaoiacid, solanine A, γ-solasonine, 7α-OH solamargine, 7α-OH khasianine, 7α-OH solasonine, β 2 -solasonine, 12β, 27dihydroxysolasodine (27-DHS) [11][12][13][14], which have been proven to be cytotoxic to a variety of cancer cells [11][12][13][14][15]. They are mainly present in immature fruits and decrease gradually to disappearance with the ripening of the fruits [16,17].…”
Section: Introductionmentioning
confidence: 99%